Valence matters: An electrophysiological study on how emotions influence cognitive performance in children. Issue 2 (13th December 2018) - Abdul Rahman, Aishah; Wiebe, Sandra A.
Abstract: Emotional stimuli have been found to influence cognitive performance in children, but it is not clear whether this effect varies with the cognitive demands of the task. In this study, we examined how emotional expressions influenced cognitive performance and event‐related potentials (ERPs) in early and middle childhood under varying cognitive control demands. Two groups of children (4.5–6.0 and 7.0–8.5 years) completed a modified flanker task where the stimuli were faces displaying task‐irrelevant emotional expressions. Emotional influence varied depending on emotional valence: Accuracy was greater for happy targets, while response time and N2 latency were longer for angry targets. In younger children only, angry targets elicited a larger late frontal negativity. Cognitive control demands did not modulate the effect of emotions on behavioral performance or ERPs, contrasting with findings in adults. Findings are discussed in relation to the dual competition model and previous work demonstrating a positivity bias in children.